ENHANCING LECTURER’S “TRI DHARMA” THROUGH PERFORMANCE MANAGEMENT SYSTEM: A STUDY AT AN INDONESIAN PRIVATE UNIVERSITY - Yuliani Rachma Putri; Syarifuddin Syarifuddin (Universitas Multimedia Nusantara, 2019)
For the last decades, Institution of Higher Learning (IHL) activities has become more complex. Competitive environment, technological advances, stakeholder and profit- oriented markets have demanded IHLs to facilitate broad areas of activities which require many resources ranging from human to technical. Thus, IHL’s managers as decision-makers faced the problems of finding the right performance measurement and the proper usage of Performance Management System (PMS) for measuring all of the performances especially for lecturers which measured by Key Performance Indicators (KPIs) known as “Tri Dharma”. Hence, this study aims to examine the use of performance management system at one faculty of an Indonesian private university. This research is the extended version from the paper presented on 3rd Icotic 2017, titled “A Study of Strategic Communication in Supporting the Performance Management System: A Case at an Indonesian Private University”. Using semi- structured interviews with 12 managers at the faculty, this study was examine how the PMS used to support lecturers in conducting the “Tri Dharma” activities by providing the guidance to reach the objectives and target of the institution. The qualitative evidence collected during the course of the research indicates that private university is now being highly competitive and it is very sensitive to changes in technology, student tastes and behaviours. In so doing, IHLs managers have to set up some suitable indicators to be measured through the Balance Score Card (BSC) as the PMS that allows faculty managerial level to translate their visions into collective visions that enhance all lecturers as teams to move in a shared-service and value-creating work. This PMS also used as a strategy map to guide with signposts and guardrails to construct and to motivate all lecturers to reach the KPIs also to maintain their performance in conducting “Tri Dharma” by linking the salary, increment, bonus to performance and make quarterly report to evaluate. Keywords: Performance Management System, Key Performance Indicators, Balance Score Card